A molecular modeling study of novel aldose reductase (AR) inhibitors - Auwal Muhammad; Kanikar Muangchoo; Ibrahim A. Muhammad; Ya'u S. Ajingi; Aliyu M. Bello; Ibrahim Y. Muhammad; Tasi'u A. Mika'il; Rakiya Aliyu (AIMS Biophysics, 2020)
Aldose reductase (AR) is an enzyme of the polyol pathway implicated in long-term effect of diabetes mellitus. The development of new molecules as drugs for the inhibition of this enzyme is a growing area of research. Several in vivo and in vitro studies have been carried out to test the inhibitory effect of many organic compounds against AR, but the results have been limited due to their weak pharmacokinetic parameters and safety profile. In this study, molecular docking and molecular dynamics (MD) simulation were performed to establish the inhibitory effect of two critical bioactive compounds (astaxanthin and zeaxanthin) that were affirmed to be safe and powerful antioxidants. Docking studies revealed that both astaxanthin and zeaxanthin displays good binding affinity and inhibition to AR with binding energies of −5.88 kcal/mol and −5.63 kcal/mol, respectively. In contrast to epalrestat; the standard inhibitor having a binding energy of −5.62 kcal/mol. Amino acid residue analysis has shown that both compounds, including the standard inhibitor, bind to the same site due to their common interaction with Trp20 and Tyr48 at AR catalytic site. To complement molecular docking results, we performed MD simulations. The results show that the binding energies of the standard inhibitor, astaxanthin, and zeaxanthin are −134.3486 kJ/mol, −186.271 kJ/mol, and −123.557 kJ/mol, respectively. In both cases, astaxanthin displays better inhibition to AR followed by the standard inhibitor and zeaxanthin.